Politically driven cycles in fiscal policy: In depth analysis of the functional components of government expenditures - Castro, Vítor (2017)
This article analyses the incidence of politically driven cycles on the functional components and sub-components of government expenditures over a group of 18 European countries during the period 1990-2012. An LSDVC estimator is employed in the empirical analysis. The results provide evidence of political opportunism at aggregated and disaggregated levels of public expenditures .. The expenditure components that have proved to be more related to that behaviour are public services, education, social protection and some sub-components of health expenditure, items that tend to generate outcomes that are more visible to voters. Some disaggregated evidence of partisan manipulation is also found.